Intellectual and Spiritual Integration in Self-Actualisationof the Naqsyabandiyah Khalidiyah Tarīqah - Muliadi; Maulani; Karim, Abdul; Wasik, Abdul; Qaaf, Muhammad Alfath (LETIGES, 2024)
This study aims to examine the interaction between intellectual and spiritual aspects in the Naqsyabandiyah Khalidiyah order and its impact on the self-actualisation and morality of the congregation. This study uses a qualitative approach with an interpretivism paradigm, focusing on the spiritual and social experiences of followers of the Naqsyabandiyah Khalidiyah Order. The study was conducted at the Naqsybandiyah Khalidiyah congregation foundation in Medan, North Sumatera, Indonesia. Data collection techniques included observation, interviews, and documentation. Data analysis was done by reduction, narrative presentation, and triangulation for validity testing. Self-actualisation through tariqah, especially in the Naqsyabandiyah Khalidiyah Order tradition, integrates intellectual and spiritual dimensions. Sheikh Kadirun Yahya developed an approach combining exact sciences with spirituality, emphasising the importance of intellectual development through an understanding of metaphysics, psychology, and deep sufism practices. This order teaches that self-actualisation depends on fulfilling physical needs and increasing spiritual awareness that connects individuals with God. Thus, Tarīqah's followers develop spiritual potential and enrich their intellect to achieve a more holistic balance in life. The implication for Islamic education is the importance of integrating intellectual and spiritual dimensions in learning. Further research suggests exploring the application of Sheikh Kadirun Yahya's teachings in Islamic education to develop students' potential holistically, both in spiritual and intellectual aspects.